2012
DOI: 10.1016/j.hrthm.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced QT-interval shortening following antiepileptic treatment with oral rufinamide

Abstract: BACKGROUND The arrhythmogenic potential of short QT intervals has recently been highlighted in patients with a short QT syndrome. Drug-induced QT-interval prolongation is a known risk factor for ventricular tachyarrhythmias. However, reports on drug-induced QT-interval shortening are rare and proarrhythmic effects remain unclear. OBJECTIVE Recently, rufinamide, a new antiepileptic drug for the add-on treatment of Lennox-Gastaut syndrome, was approved in the European Union and the United States. Initial trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 43 publications
1
33
0
6
Order By: Relevance
“…In a recent study, Schimpf et al (556) reported that the antiepileptic drug rufinamide caused ϳ20 ms shortening of corrected QT interval in a sample of 19 patients. There were, however, no adverse events (cardiac arrhythmias or sudden cardiac arrest) observed in this group over an average 3-yr follow up.…”
Section: Clinical Managementmentioning
confidence: 99%
“…In a recent study, Schimpf et al (556) reported that the antiepileptic drug rufinamide caused ϳ20 ms shortening of corrected QT interval in a sample of 19 patients. There were, however, no adverse events (cardiac arrhythmias or sudden cardiac arrest) observed in this group over an average 3-yr follow up.…”
Section: Clinical Managementmentioning
confidence: 99%
“…It has been associated with mutations in potassium channels genes KCNH2, KCNQ1, and KCNJ2, leading to earlier repolarization, atrial arrhythmias, syncope, and sudden death (Brugada et al, 2004;Hong et al, 2005;Priori et al, 2005). Some antiepileptic medications like rufinamide may promote QTc shortening (Schimpf et al, 2012).…”
Section: Short Qt Syndromementioning
confidence: 99%
“…While the extent of decrease was small and would not bring a normal QTc into the range associated with arrhythmias in the short QT syndrome 10 , it does raise the question of risk that might be related to more substantial drug-induced QT shortening. We are not aware of any clearly documented instances of arrhythmias arising from drug-induced QT shortening, and drugs that do substantially reduce QTc are in clinical use 11 . Nevertheless, some investigators recommend caution 12 .…”
Section: Discussionmentioning
confidence: 99%